PENGARUH PEMBERIAN WALKING ON THE SPOT EXERCISE TERHADAP PENINGKATAN KEBUGARAN FISIK PADA PENDERITA HIPERTENSI DI KELOMPOK LANSIA PUSKESMAS SANDEN BANTUL - Ummy A'isyah Nurhayati (Departemen of Health Policy and Management, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2025)
Background: Elderly is a term used to describe people who undergo biological, physical and social changes as they age. Hypertension has become a common health problem in Indonesia. In Bantul Regency in 2020, there were 83,932 cases of hypertension from the total population. Walking is a form of low- to moderate-intensity aerobic exercise that most people can do easily and with minimal risk. Walking can improve cardiorespiratory fitness, muscle strength and body composition in older people. By measuring the 6MWT, a fitness level can be obtained which becomes a database for determining exercise programmes and interventions that are appropriate to the cardiorespiratory capacity of elderly hypertensive patients. Objectives: This study investigates the impact of walking on the spot exercise, on enhancing physical fitness in hypertensive patients in the elderly group of Puskesmas Sanden Bantul. Methods: Experimental research with a group pretest-posttest design. The sampling technique was purposive sampling. The number of samples is 30 people who are members of